2018
DOI: 10.1111/evj.12842
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of digital cryotherapy using a commercially available sleeve style ice boot in healthy horses and horses receiving i.v. endotoxin

Abstract: The boot caused significant decreases in lamellar temperatures compared with untreated control limbs in all horses. Endotoxaemic horses had significantly colder lamellae and skin than healthy horses. This study is the first to show that a sleeve style boot, where ice does not cover the hoof, can cause significant decreases in lamellar temperatures through cooling of blood as it travels to the foot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…10 In our study, neorickettsiosis cases were significantly more likely to present with or to develop laminitis than coronavirus and unknown cases, despite the widespread use of digital cryotherapy in colitis cases in our hospital. Recent literature has compared various methods for digital cryotherapy, and while 1 study found that the commercially available sleeve-style ice boot used in our hospital achieved appropriately low skin and lamellar temperatures, 13 another study found that this sleeve-style boot did not maintain hoof surface temperatures below 10 C. 14 It is possible that the combination of variably effective cryotherapy method, warm ambient temperature seen in summer when neorickettsiosis cases are most common, as well as the fact that some cases presented to the hospital already showing signs of laminitis, contributed to the high incidence of laminitis in our study. Beyond the study evaluating digital cryotherapy in colitis cases, 10 the majority of studies evaluating methods of digital cryotherapy are performed in ideal research settings, and one can question how these results translate to clinical practice.…”
Section: Survivalmentioning
confidence: 91%
“…10 In our study, neorickettsiosis cases were significantly more likely to present with or to develop laminitis than coronavirus and unknown cases, despite the widespread use of digital cryotherapy in colitis cases in our hospital. Recent literature has compared various methods for digital cryotherapy, and while 1 study found that the commercially available sleeve-style ice boot used in our hospital achieved appropriately low skin and lamellar temperatures, 13 another study found that this sleeve-style boot did not maintain hoof surface temperatures below 10 C. 14 It is possible that the combination of variably effective cryotherapy method, warm ambient temperature seen in summer when neorickettsiosis cases are most common, as well as the fact that some cases presented to the hospital already showing signs of laminitis, contributed to the high incidence of laminitis in our study. Beyond the study evaluating digital cryotherapy in colitis cases, 10 the majority of studies evaluating methods of digital cryotherapy are performed in ideal research settings, and one can question how these results translate to clinical practice.…”
Section: Survivalmentioning
confidence: 91%
“…Burke et al evaluated the same ice boot that incorporates the distal limb but not the hoof using a different methodology, reasoning that the popularity of this boot in various equine hospitals warranted further evaluation of its ability to provide digital hypothermia. They measured lamellar temperatures by inserting thermocouples into the dorsal lamellae of the forelimbs.…”
Section: What Methods Should Be Used To Apply Digital Cryotherapy?mentioning
confidence: 99%
“…Continuous therapeutic cooling, known as 'cryotherapy' or 'digital hypothermia' , has been shown in experimentally induced laminitis models, to reduce the severity of laminitis (Bamford, 2019;Burke et al, 2018;Reesink et al, 2012;Van Eps & Orsini, 2016;Van Eps & Pollitt, 2010). In addition to providing analgesia, hypothermia has been shown to inhibit invasion of damaging activated leucocytes into the laminae of critical patients (Hurcombe & Holcombe, 2017;Worster et al, 2000).…”
Section: Cryotherapy or Digital Hypothermiamentioning
confidence: 99%